Napredni mehatronski postopek načrtovanja odprtega krmilja strojev - Hace, Aleš (Strojniški vestnik, 2004)
This paper addresses the field of factory automation within the scope of flexible production systems. It presents a new mechatronic approach to machinecontrol, which introduces an integrated and interdisciplinary method toholistic machine design. The mechanical, electronic and informatics aspects of a production system are involved synergistically. The paper describes a distributed control architecture for a cutting machine. In addition, it applies a new approach to the development of control functions. The controllerwas built on the open QNX real-time operating system for the PC architecture. The commonly accepted graphical-user-interface environment of Microsoft Windows serves as the front-end of the HMI. The controller and the HMI are interconnected by an Ethernet TCP/IP link that is extended to the office-level of factory automation. A new method for describing logic control functions introduces a modular logic controller that is specified and formalized using a matrix representation of Petri nets. It allows a system simulation and an off-line analysis that can significantly shorten a machine control development cycle. The new method is compatible with standard programming languages for logic controllers. Furthermore, it represents a basis for the design of more efficient, reliable, and user-friendly machine control.
Keywords: avtomatizacija proizvodnje; RNK-PLK; sistemi operacijski časovno realni; sistemi vodenja; mreže Petri; mehatronika; načrtovanje; rezalno orodje; Petrijeve mreže